Orthodontic treatment finishing with minimally invasive resin composite veneers. - Maenosono, Rafael Massunari; Ramos, Carla Muller; Brianezzi, Letícia Ferreira de Freitas; Oda, Denise Ferracioli; Mondelli, Rafael Francisco Lia; Ishikiriama, Sérgio Kiyoshi (Brazilian Dental Science, 2015)
Anatomic alterations caused by incisal guide wear, even being small, cause the aspect of an aged smile. The objective of this clinical case is to report a highly conservative esthetical treatment, performed through the association of in-office bleaching and resin composite veneers. In-office bleaching was performed with 35% hydrogen peroxide, and in the following week minimal invasive resin composite veneers were implemented on upper incisors and canines. In the next appointment, finishing and polishing were performed with abrasive discs and silicon carbide brushes. The results were considered highly satisfactory, determining a younger aspect of the patient’s smile. Resin composite veneers are still an excellent alternative for esthetical reanatomization of anterior teeth, being capable to generate optimized results with low costs and time.